Three new species of the aphaenopsian trechine genus Pilosaphaenops Deuve & Tian, 2008 from South China Karst (Coleoptera: Carabidae: Trechinae). Issue 3 (3rd May 2020) - Huang, Sunbin; Tian, Mingyi; Faille, Arnaud
Summary: Three new trechine species of the genus Pilosaphaenops Deuve & Tian, 2008, P. qianzhii n. sp . from cave Lubian Dong in Pingtang County, southern Guizhou Province, P. mengzhenae n. sp . and P. weiguofui n. sp . from cave Xia Dong in Nandan County, and cave Shenlong Gong in Huanjiang County respectively, northern Guangxi Zhuang Autonomous Region, are described and illustrated. A key to all known species of this genus is also provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:170C467F-5421-49AD-B1B1-091D8BD58B88